Blood vessel epicardial substance reduces LRP6 receptor and cytoplasmic β-catenin levels to modulate Wnt signaling and intestinal homeostasis. (23rd January 2019) - Thompson, Joshua J; Short, Sarah P; Parang, Bobak; Brown, Rachel E; Li, Chenxuan; Ng, Victoria H; Saito-Diaz, Kenyi; Choksi, Yash A; Washington, Mary K; Smith, Jesse Joshua; Fingleton, Barbara; Brand, Thomas; et al.
Abstract: Blood vessel epicardial substance (BVES, otherwise known as POPDC1) is an integral membrane protein known to regulate tight junction formation and epithelial–mesenchymal transition. BVES is underexpressed in a number of malignancies, including colorectal cancer. BVES loss leads to activation of the Wnt pathway, suggesting that decreased BVES expression functionally contributes to tumorigenesis. However, the mechanism by which BVES modulates Wnt signaling is unknown. Here, we confirm that BVES loss increases β-catenin protein levels, leads to Wnt pathway activation in a ligand-independent fashion and coordinates with Wnt ligand to further increase Wnt signaling. We show that BVES loss increases levels and activation of the Wnt co-receptor, LRP6, in cell lines, murine adenoma tumoroids and human-derived colonoids. We also demonstrate that BVES interacts with LRP6. Finally, murine tumor modeling using a Wnt-driven genetic model and a chemically induced model of colorectal carcinogenesis demonstrate that BVES loss increases tumor multiplicity and dysplasia. Together, these results implicate BVES as an inhibitor of Wnt signaling, provide one of the first examples of a tight junction-associated protein regulating Wnt receptor levels, and expand the number of putative molecular targets for therapeutic intervention in colorectal cancer. Abstract : Alterations in Wnt signaling are fundamental drivers of cancer. We identified an unexpected interaction between BVES and the Wnt co-receptor LRP6 and show that loss of BVES increases receptor activation, Wnt signaling and intestinal tumorigenesis.